Reliability and construct validation of the Filipino version of the modified checklist for autism in toddlers (M-CHAT FV) - Tanchanco, Lourdes Bernadette S. (2015.)
Background: Autism is a complex neurodevelopmental disorder that presents with impairments in social communication and repetitive behavior. Early detection and intervention improves outcomes of children. No autism-specific screening tool has been validated in the Philippines.
Objectives: To develop a valid and reliable autism-specific screening tool for 18 to 48 month old Filipino children that can be used by general pediatricians in the primary care setting.
Methods: The Modified Checklist for Autism in Toddlers was translated to Filipino and back translated to English. Face and content validation were done, as well as reliability testing. Construct validation using the Item Response Theory was also conducted.
Results: After initial face and content validation of the translated Modified Checklist for Autism in Toddlers: Filipino Version (M-CHAT:FV) questionnaire was done, the caregivers of 252 toddlers were asked to respond to the questionnaire. Tests for reliability revealed good internal consistency, with the Cronbach alpha of 0.79 and the Theta reliability of 0.95 both being above the cut-offs of 0.6 and 0.90, respectively. Item Response Theory was used to analyze the results since only one latent trait ? autism ? was identified in the questionnaire. Using item difficulty and item discrimination parameters, six questions were deemed non-significant and removed from the original 23-item M-CHAT questionnaire. The resulting 17-item M-CHAT:FV demonstrated good model fit, with a root mean square error of approximation (RMSEA) of 0.04 (cut off< 0.06) and a Comparative Fit Index of 0.94 (cut off> 0.90) based on Model Fit Information analysis.
Conclusion: The 17-item M-CHAT:FV has good reliability, and good face and content validity, when used as an autism-specific screening tool among Filipino children aged 18 to 48 months seen in the primary health care setting. Construct validation shows that M-CHAT:FV is a unidimensional tool pointing to one latent trait, autism. It has high item difficulty and can discriminate well between those with "high" autism traits and "low" autism traits. Criterion validation will still need to be done before it can be recommended for use among general pediatricians and primary physicians in the primary care setting.
Thesis (Master of Science in Epidemiology (Clinical Epidemiology))--University of the Philippines Manila
Keywords: Autism in children--Detection.